2019
DOI: 10.3347/kjp.2019.57.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Previous Infection with Plasmodium berghei Confers Resistance to Toxoplasma gondii Infection in Mice

Abstract: Both Plasmodium spp. and Toxoplasma gondii are important apicomplexan parasites, which infect humans worldwide. Genetic analyses have revealed that 33% of amino acid sequences of inner membrane complex from the malaria parasite Plasmodium berghei is similar to that of Toxoplasma gondii. Inner membrane complex is known to be involved in cell invasion and replication. In this study, we investigated the resistance against T. gondii (ME49) infection induced by previously infected P. berghei (ANKA) in mice. Levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another explanation could be that the persistent installation of T. gondii in its host involves a dynamic regulation of combined cellular and molecular immunoregulatory networks [52][53][54][55], which can impact the newly infecting Plasmodium parasite using similar pathways. This could result in less production of anti-PfAMA1 IgG to effectively fight plasmodial parasites.…”
Section: Plos Onementioning
confidence: 99%
“…Another explanation could be that the persistent installation of T. gondii in its host involves a dynamic regulation of combined cellular and molecular immunoregulatory networks [52][53][54][55], which can impact the newly infecting Plasmodium parasite using similar pathways. This could result in less production of anti-PfAMA1 IgG to effectively fight plasmodial parasites.…”
Section: Plos Onementioning
confidence: 99%
“…gondii ME49 strain, which includes VLPs co-expressing the inner membrane complex (IMC), rhoptry protein 18 (ROP18), and microneme protein 8 (MIC8) [ 25 , 32 , 45 ]. Other VLPs co-displaying the ROP4 and ROP13 antigens [ 31 , 46 ] or the MIC8 and ROP18 antigens have been generated and their efficacies were evaluated in mice [ 20 ]. Surprisingly, the CST1 VLPs generated in this study demonstrated the strongest brain cyst inhibition, surpassing those reported in our previous works.…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after the boost immunization, mice were orally challenge-infected with 450 T . gondii ME49 cysts as previously described [ 31 ]. Briefly, the brain tissues of T .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations